A NOVEL APPROACH TO DYNAMIC CIRCUIT CONFIGURATION IN THE TOR NETWORK FOR TRAFFIC ANONYMIZATION: A NOVEL APPROACH TO DYNAMIC CIRCUIT CONFIGURATION IN THE TOR NETWORK FOR TRAFFIC ANONYMIZATION - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This scientific article presents a new approach for dynamically configuring Tor circuits in response to real-time network conditions and potential threats. In contrast to the traditional static path selection used in Tor, the proposed method applies an adaptive algorithm that selects relay nodes according to both anonymity and performance criteria. The system was tested in simulated network environments under different adversarial scenarios. The results show a clear decrease in the likelihood of traffic correlation attacks when compared with the default Tor protocol. Overall, the approach offers a practical way to strengthen the anonymity and stability of the Tor network while maintaining acceptable performance levels.